STRATEGI IMPLEMENTASI MODEL PENGEMBANGAN WIRAUSAHAWAN MUDA BAGI MASYARAKAT PESISIR KABUPATEN TAKALAR - Abdul Rahman Rahim; Ismail Rasulong; Edi Jusriadi; Faidul Adzim (BALANCE: Economic, Business, Management and Accounting Journal, 2017)
ABSTRACT  The aims of the research are: (1) reviewing and analyzing the strategy of applying the model of developing young entrepreneurs through the container of a business incubator. (2) the role and commitment of the actors (government, financial institutions, youth professional organizations, village government, community leaders, youth organizations, and private sector) in a broader partnership network to support the implementation of young entrepreneurship in development models through the container of a business incubator for coastal communities.The data collection through in-depth interviews, potential mapping, and focus group discussions with the stakeholder, in this case, the main actors of development includes government, financial institutions, professional organizations of young entrepreneurs, community leaders, youth organizations, and private parties including universities. This qualitative research data analysis activity is done interactively and continuously until complete through several steps of activity systematically, that is collection/ data record, data reduction, data presentation, Verification and drawing the Conclusion.The conclusions of this research are the formulation of trial strategy in applying the young entrepreneur development model through the container of a business incubator.  Start by the strengthening of commitment among the actors, the formulation of a module for training, the formation of planning action, forming the team, training module, module for mentoring, and each of the main actors for a business incubator. The next step is doing an inventory of prospective new entrepreneurs and beginner entrepreneurs who will be fostered and developed through the container of a business incubator. The Structured training is for new groups of entrepreneurs and starting-up the new entrepreneurs from youth groups. The mentoring of business groups that initiated from the training results, and business incubators in bridging new business groups for access to capital and market access.Keywords : Coastal Communities, Young Entrepreneurs, Business IncubatorsCorrespondence to : rahman.rahim@unismuh.ac.id, ismail.rasulong@unismuh.ac.id, edi.jusriadi@unismuh.ac.id, faidul.adzim@unismuh.ac.id  ABSTRAK   Tujuan Penelitian ini, yaitu: (1) mengkaji dan menganalisis strategi penerapan model pengembangan wirausahawan muda melalui wadah inkubator bisnis; (2) menganalisis peran dan komitmen lintas aktor (pemerintah, lembaga keuangan, organisasi profesi pengusaha muda, pemerintah desa, tokoh masyarakat, organisasi kepemudaan, dan pihak swasta) dalam jaringan kemitraan yang lebih luas untuk mendukung implementasi model pengembangan wirausahawan muda melalui wadah inkubator bisnis bagi masyarakat pesisir.Pengumpulan data melalui wawancara mendalam dan focus group discussion (FGD) dengan pihak-pihak terkait dalam hal ini aktor utama pembangunan meliputi pemerintah, lembaga keuangan, organisasi profesi pengusaha muda, pemerintah desa, tokoh masyarakat, organisasi kepemudaan, dan pihak swasta termasuk perguruan tinggi. Analisis data penelitian menggunakan metode kualitatif yang dilakukan melalui beberapa langkah secara sistematis, yakni Koleksi/Catatan data, Reduksi data, Penyajian data, Verifikasi dan penarikan kesimpulan.Simpulan dari penelitian ini adalah Rumusan strategi uji coba penerapan model pengembangan wirausahawan muda melalui wadah inkubator bisnis harus dimulai dengan adanya peneguhan komitmen antar lintas aktor, perumusan modul pelatihan, pembentukan tim penyusun rencana aksi, modul pelatihan, modul pendampingan, dan penyusunan detail peran masing-masing aktor utama inkubator bisnis. Selanjutnya melakukan inventarisasi calon-calon wirausahawan baru dan wirausahawan pemula yang akan dibina dan dikembangkan melalui wadah inkubator bisnis. Pelatihan terstruktur bagi kelompok wirausahawan baru dan wirausahawan pemula dari kelompok pemuda. Pendampingan kelompok-kelompok usaha yang telah digagas dari hasil pelatihan, dan pihak inkubator bisnis menjembatani kelompok-kelompok usaha baru untuk akses permodalan dan akses pasar.Kata kunci : Penerapan Model, Wirausahawan Muda, Inkubator Bisnis, Masyarakat PesisirKorespondensi : rahman.rahim@unismuh.ac.id, ismail.rasulong@unismuh.ac.id, edi.jusriadi@unismuh.ac.id, faidul.adzim@unismuh.ac.id